2018
DOI: 10.1016/j.joca.2018.02.896
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical total shoulder arthroplasty used for glenohumeral osteoarthritis has higher survival rates than hemiarthroplasty: a Nordic registry-based study

Abstract: Anatomical TSA had the highest implant-survival rate. Young patients had, independently of the arthroplasty type, lower implant-survival rates. The treatment of young patients with end-stage osteoarthritis remains a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…The incidence of total shoulder arthroplasty (TSA) is increasing with population growth, aging, and the concomitant increase in prevalence of glenohumeral osteoarthritis (OA) [1][2][3][4]. Since the 1970s and the implantation of the first contemporary total shoulder prostheses, issues with radiolucent lines around glenoid components and aseptic loosening have been observed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of total shoulder arthroplasty (TSA) is increasing with population growth, aging, and the concomitant increase in prevalence of glenohumeral osteoarthritis (OA) [1][2][3][4]. Since the 1970s and the implantation of the first contemporary total shoulder prostheses, issues with radiolucent lines around glenoid components and aseptic loosening have been observed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Their 10-year cumulative arthroplasty survival rate was 0.75. The authors concluded that the results support the use of anatomical total shoulder arthroplasty for all ages [10].…”
Section: Arthroplasty Survival Ratesmentioning
confidence: 73%
“…On the other hand, there are several publications that observed an increased risk for revision with lower age. 14 , 18 , 23 Wagner et al 23 found a clear negative correlation of age and revision risk and described for every increase in 1 year of age a 3% decreased risk of revision surgery and a 13% decreased risk of revision surgery for mechanical implant failure based on the analysis of prospectively collected data of 5494 consecutive shoulder arthroplasties performed from 1970 to 2012.…”
Section: Discussionmentioning
confidence: 99%